A methods engineering study on Metro Container Corporation - Guan Hing, Dianne Mae (College of Engineering, 2004)
METRO CONTAINER CORPORATION (METROCAN), a family-owned enterprise, started as a backyard business prior to its incorporation on March 16, 1973. It had the primary purpose of engaging and carrying on the business of manufacturing, selling and distributing on a wholesale basis, plain and lithographed packaging materials of every kind, description and character for use in the transportation and preservation of goods in commerce, and to conduct and carry all other business pertaining there to. Presently, Metrocan has 300 competent and well-trained personnel in its workforce. Two (2) strategic can-forming facilities, located at Mapulang Lupa, Valenzuela and Manggahan, Pasig City, cater to a wide array of application in various can shapes, dimensions, and designs. The group has limited its studies to only the Printing or Lithography Stage of the whole tin can production system, particularly those done on machine 4 where most of the lithography processes (printing, lacquering, coating and varnishing) could be performed. Lithography is a vital part of the production process because it is the primary operation that utilizes 3 out of 5 raw materials for tin can manufacture tin plates, coating and lacquer. It is therefore imperative that maximum productivity is achieved by this operation. The main concerns of Metro Container Corporation are to minimize set-up and changeover time to decrease delay, decrease worker idle time, and to increase overall printing production. From the problems identified we came up with six causes of the above mentioned concerns and one problem on Work Conditions, namely No Standard Time and Job Assignments for Changeover; No Standard Procedure for Mixing Paint; High Rejection Rate; Worker Idle Time and Unequal Workload Distribution; Unnecessary Machine Parts; Plant Layout Problem; and Worker Fatigue. The group made use of the concepts and techniques of Methods Engineering to come up with recommendations for the improvement of the company. An area of concern in the printing process is the set up and/or changeover time, since observations made on the changeover process show that there is no standard procedure and therefore, no standard time, causing delay. The group decided to use time study to establish time standard, arriving at the standard setup/changeover time of 52.44 minutes. The group also observed that there is no standard procedure for mixing paint. Much delay in printing time is caused when many adjustments have to be made in the paint mixture before the right color is obtained. The group recommends the establishment of the right amount of paint to be used for the color mixture for every color of every design. After, measuring devices or apparatuses shall be used every time the process of mixing paint is to be done. Purchasing these would amount to a cost of approximately Php3,000.00. About two percent of the total production and a large part of the percentage of rejects are put to waste due to printing defects. Smears (stains), misregistrations (misalignment), under standard color (not within color swatch reference), and scratches are but some of the few defects identified by the company. With proper worker information, standardization of procedures and more careful handling, the number of rejects can be greatly reduced. Training and QA personnel will be taking part in the implementation of this recommendation. Unequal workload distribution among the four printing personnel was also observed with the Feeder and Harvester incurring a lot of idle time. Two alternatives were presented, Job Enlargement and Reduction of Number of Workers to Three. The latter was chosen because it posed the benefits of improved workloads distribution and additional benefits of reduced labor cost and increased worker satisfaction and efficiency. In our chosen area of concentration, machine 4, it was observed that there were unnecessary machine parts like the Printing Cylinder 1 and the UV Drier, since these parts were not being utilized in the printing process. It was observed that there was an unavoidable length of travel time and distance for each tin plate as it travels through the machine. The group recommends the removal of these parts for long term benefit. The cost of removal would amount to approximately Php10,000.00. About four fifths of the printing process is spent inside the printing machine line. When the group conducted time studies for the lithography process, the delivery of stacked plates to and from the location was also recorded. Time study data revealed huge quantities of time delay due to delivery so the group figured two proposals to solve the problem. One consists of painting a regular route for the forklifts as to be guided and obstructions be removed out of the path's way. Also, this recommendation suggests of a more orderly workplace. The alternative involves a major renovation of the warehouse. Briefly, it would involve creating a new entry point at the warehouse's side. Studying the structure, it is feasible to perform the change. This proposal greatly cuts the transport distance traveled. Cost benefit analysis was also performed and results favor the latter proposal with an estimated cost of Php 30,000.00. Restructuring should take two weeks at pessimistic assumptions. Finally, the group addressed the problem of poor work condition that contribute greatly to worker fatigue. This includes the high room temperature, cluttered work area and the lack of proper stools to sit on. The group recommends the addition of ventilators, (approximately 400.00 each), industrial fans (approximately 365.00 each), repainting of the machine (Php1,000.00), formation of a Maintenance Team (Php31.67/hr/worker) and the provision of well conforming stools for each worker (66.62). The implementation of all the recommendations are estimated at 6 weeks, covering all information dissemination among the management and personnel involved, purchasing of needed materials, training, actual implementation and observation period. Follow up of the newly installed methods must come after in order to ensure the compliance of all parties involved. For future studies and methods improvement plans, the management may look into synchronous servicing and or machine coupling to maximize the use of machines once the company has already picked up on the improvements mentioned above.